The analysis of Java ORM frameworks performance in terms of analytical data processing - Justyna Baran; Piotr Muryjas (Journal of Computer Sciences Institute)
The aim of this paper is to evaluate Java ORM frameworks in terms of analytical data processing. The analysis includes following technologies: Hibernate, Apache Cayenne, EclipseLink and DataNucleus. Article contains characteristics and importance of ORM technologies, as well as the research of related literature. The main study has been performed with the use of implemented Java applications that enabled to run and measure the execution time of analytical queries with various levels of complexity. The analysis of the obtained results enabled to define Hibernate as the most efficient technology for analytical data processing. Additionally the limitations of examined tools and the significant differences between them have been identified and presented.